Assessment of Steady and Unsteady Full Annulus Simulations Predictivity for a Low-Speed Axial Fan at Load-Controlled Windmill - Aurélie Ortolan; Suk-Kee Courty-Audren; Nicolas Binder; Xavier Carbonneau; Yannick Bousquet; Florent Challas (International Journal of Rotating Machinery)
A steady mixing plane approach is compared with the time-averaged solution of an unsteady full annulus calculation for a conventional fan operating at load-controlled windmill. The objective is to assess the added value of a complete unsteady calculation compared with a more classical approach, especially concerning the effect of the spatial and temporal periodicity release in such an unusual operation as windmill. Experiment with global steady measurements and rotor radial characterizations was conducted. Numerical analysis demonstrates that windmilling global performances obtained with the time-averaged solution of the unsteady simulation are not far different from the steady case, especially in the rotor. Some differences arise in the stator, particularly regarding the velocity field. Temporal periodicity release in this row has clearly a significant effect on the flow unsteady response. A detailed analysis highlights that generic patterns of windmilling flows recorded on a steady approach are also reported on the unsteady case.